Supporting Inclusive Design of Mobile Devices with a Context Model - Kirisci, Pierre T.; Thoben, Klaus-Dieter; Klein, Patrick; Hilbig, Martin; Modzelewski, Markus; Lawo, Michael; Fennell, Antoinette; O’Connor, Joshue; Fiddian, Thomas; Mohamad, Yehya; Klann, Markus; Bergdahl, Thomas; et al. (IntechOpen, 2012)
None